Optimisme dalam Lirik Lagu Vairus Corona oleh Muhammad Romadhon - Rahmawati, Isnaini; Choironi, Merry (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2024)
The article entitled "Optimism in the lyrics of the song Vairus Corona by Muhammad Romadhon" is an article that talks about Arabic songs that were present during the co-19 pandemic. Departing from the author's desire to reveal the optimistic side that the musician brings to motivate the audience, the researcher intends to reveal the symbols of optimism in the song with Riffaterre's Semiotics approach where data is collected by reading and recording techniques, analysis is carried out by reading heuristics, hermeneutics, matrix searches and hypograms. The findings obtained are in the form of reading the song text based on linguistic analysis in the heuristic trick followed by a hermeneutic method with the disclosure of noncontinuity of expression in the form of the use of majas, metaphors, contradictions and repetitions. Universally, the meaning stated in the song lyrics is an invitation to believe in oneself, adhere to health protocols, have collective responsibility, maintain family health and safety, believe in God's help and still have hope that God will provide solutions for His servants who are brave and confident in His Power.